Sonographic Evaluation of the Endotracheal Tube Position in the Neonatal Population: A Comprehensive Review and Meta-Analysis - Congedi, Sabrina; Savio, Federica; Auciello, Maria; Salvadori, Sabrina; Nardo, Daniel; Bonadies, Luca (Frontiers in Pediatrics, 2022)
Background Endotracheal intubation in neonates is challenging and requires a high level of precision, due to narrow and short airways, especially in preterm newborns. The current gold standard for endotracheal tube (ETT) verification is chest X-ray (CXR); however, this method presents some limitations, such as ionizing radiation exposure and delayed in obtaining the radiographic images, that point of care ultrasound (POCUS) could overcome. Primary Objective To evaluate ultrasound efficacy in determining ETT placement adequacy in preterm and term newborns. Secondary Objective To compare the time required for ultrasound confirmation vs. time needed for other standard of care methods. Search Methods A search in Medline, PubMed, Google Scholar and in the Cochrane Central Register of Controlled Trials (CENTRAL) was performed. Our most recent search was conducted in September 2021 including the following keywords: “newborn”, “infant”, “neonate”, “endotracheal intubation”, “endotracheal tube”, “ultrasonography”, “ultrasound”. Selection Criteria We considered randomized and non-randomized controlled trials, prospective, retrospective and cross-sectional studies published after 2012, involving neonatal intensive care unit (NICU) patients needing intubation/intubated infants and evaluating POCUS efficacy and/or accuracy in detecting ETT position vs. a defined gold-standard method. Three review authors independently assessed the studies' quality and extracted data. Main Results We identified 14 eligible studies including a total of 602 ETT evaluations in NICU or in the delivery room. In about 80% of cases the gold standard for ETT position verification was CXR. Ultrasound was able to identify the presence of ETT in 96.8% of the evaluations, with a pooled POCUS sensitivity of 93.44% (95% CI: 90.4–95.75%) in detecting an appropriately positioned ETT as assessed by CXR. Bedside ultrasound confirmation was also found to be significantly faster compared to obtaining a CXR. Conclusion POCUS appears to be a fast and effective technique to identify correct endotracheal intubation in newborns. This review could add value and importance to the use of this promising technique.